TRANSFORMASI SOSIAL DAN POLITIK DI NEGARA-NEGARA MUSLIM: STUDI KASUS NEGARA-NEGARA MUSLIM - Mhd. Fariz Haikal Yahya; Fahrezy Ramadhan; Muhammad Iffandra Abrory (CV. Denasya Smart Publisher, 2025)
This article discusses case studies of three Muslim countries that implement different government systems, namely Saudi Arabia, Iran and Türkiye, to illustrate the diversity of political models in the Islamic world. Saudi Arabia adheres to an Islamic Monarchy system, where power is fully held by the royal family which is supported by religious legitimacy based on Sharia and Wahhabism. In contrast, Iran implemented an Islamic Republic system combined with the Regional al-Faqih doctrine, making clerical authority the center of political control.